Power System State Estimation Bad Data Detection and Identification: A Review on Issues and Alternative Formulations - Nurul Fauzana Imran Gulcharan; Nursyarizal Mohd Nor; Taib Ibrahim; Hanita Daud (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
State Estimation (SE) is the main function of power system where Energy Management System (EMS) is obliged to estimate the available states. Power system is a quasi-static system and hence changes slowly with time. Dynamic State Estimation (DSE) technique represents the time deviation nature of the system, which allows the forecasting of state vector in advance. Various techniques for DSE are available in the literature. This paper presents a review on different methodologies and developments in DSE, based on comprehensive survey of the available literature. From the survey it can be concluded that there are still areas in the developing DSE that can still be improved in terms of system computational time, redundancy and robustness of the system.